WEB PORTAL LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN (LPMK) INFORMATION SYSTEM IN SEMARANG CITY GOVERNMENT - Asy SY Prayitna; Sasongko Budi (President University, 2022)
Semarang City is the Capital of CentralJava Province, its stands for 16 Kecamatan and 177Kelurahan. for organizing the empowerment of eachKelurahan The Semarang City Government createThe Lembaga Pemberdayaan Masyarakat Kelurahan(LPMK) is a forum formed on the initiative of thecommunity as a partner of the Regional Governmentin accommodating and realizing the aspirations andneeds of the community in the field of development